2017
DOI: 10.1002/chem.201701617
|View full text |Cite
|
Sign up to set email alerts
|

Fluidic Manufacture of Star‐Shaped Gold Nanoparticles

Abstract: Star-shaped gold nanoparticles (StarAuNPs) are extremely attractive nanomaterials, characterized by localized surface plasmon resonance which could be potentially employed in a large number of applications. However, the lack of a reliable and reproducible synthetic protocols for the production of StarAuNPs is the major limitation to their spreading. For the first time, here we present a robust protocol to manufacture reproducible StarAuNPs by exploiting a fluidic approach. Star-shaped AuNPs have been synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 46 publications
1
39
0
Order By: Relevance
“…Microfluidic systems offer accurate control of various experimental parameters, such as sample volume, flow rate, mixing velocity, reaction time and temperature, providing a significantly more precise way to optimize the physical properties and hence imaging performance of SERS nanoprobes [78]. As such, microfluidic systems with different flow profiles, specifically continuous and segmented (or droplet) flows, have been used to produce a range of plasmonic nanostructures including gold nanostars which have been used as plasmonic cores of SERS nanoprobes [80][81][82][83][84][85].…”
Section: Synthesis In Microfluidic Devicesmentioning
confidence: 99%
“…Microfluidic systems offer accurate control of various experimental parameters, such as sample volume, flow rate, mixing velocity, reaction time and temperature, providing a significantly more precise way to optimize the physical properties and hence imaging performance of SERS nanoprobes [78]. As such, microfluidic systems with different flow profiles, specifically continuous and segmented (or droplet) flows, have been used to produce a range of plasmonic nanostructures including gold nanostars which have been used as plasmonic cores of SERS nanoprobes [80][81][82][83][84][85].…”
Section: Synthesis In Microfluidic Devicesmentioning
confidence: 99%
“…145,146 Silvestri et al demonstrated millifluidic synthesis of gold nanostars through a seedless, silver-mediated synthesis. 143 The final nanostar morphology was highly influenced by flow rate; slower flux rate caused inefficient mixing resulting in polydisperse product while higher flux rate yielded large nanocrystals and clusters. Another group obtained star-like gold nanosystem intermediates by adjusting the pH of the reaction through increased flow rate of an alkaline growth solution.…”
Section: Microfluidic Synthesismentioning
confidence: 99%
“…Each single batch can be different from the others as too many parameters control the morphology, size and stability of NPs. In order to overcome these issues a microfluidic protocol was developed to produce, for the first time, multibranched gold nanoparticles at room temperature and avoiding the use of toxic template ( Figure 7 ) [ 56 ]. The methodology is based on the accurate mixing of gold precursor (HAuCl 4 ) and ascorbic acid as reducing agent, in a proper ratio and with a flux fixed at 5 mL/min, while the fine control of the morphology was achieved by adding silver nitrate.…”
Section: Synthesismentioning
confidence: 99%
“…Right: ( A ) TEM image of a single multibranched gold nanoparticle immobilized on titania; ( B ) HR-TEM image of a single branch interacting with a titania. Reproduced from [ 56 ] with permission from John Wiley and Sons.…”
Section: Figurementioning
confidence: 99%